Versatile Mitogenic and Differentiation‐Inducible Layer Formation by Underwater Adhesive Polypeptides. Issue 16 (26th June 2021) - Tada, Seiichi; Ren, Xueli; Mao, Hongli; Heo, Yun; Park, Shin‐Hye; Isoshima, Takashi; Zhu, Liping; Zhou, Xiaoyue; Ito, Reiko; Kurata, Shino; Osaki, Megumi; Kobatake, Eiry; et al.
Abstract: Artificial materials have no biological functions, but they are important for medical devices such as artificial organs and matrices for regenerative medicine. In this study, mitogenic and differentiation‐inducible materials are devised via the simple coating of polypeptides, which contain the sequence of epidermal growth factor or insulin‐like growth factor with a key amino acid (3, 4‐dihydroxyphenylalanine) of underwater adhesive proteins. The adhesive polypeptides prepared via solid‐phase synthesis form layers on various substrates involving organic and inorganic materials to provide biological surfaces. Through the direct activation of cognate receptors on interactive surfaces, the materials enable increased cell growth and differentiation compared to that achieved by soluble growth factors. This superior growth and differentiation are attributed to the long‐lasting signal transduction (triggered by the bound growth factors), which do not cause receptor internalization and subsequent downregulation. Abstract : 3, 4‐dihydroxyphenylalanine‐containing peptides form bioactive layers on organic and inorganic material surfaces. On the adhesive growth factor nanolayers, cells receive long‐term biological signals from immobilized growth factors, leading to improved cell growth and differentiation.